Public Education, university autonomy and political change: Notes for the analysis of the university movement in Chile, 2011 - Molina Bravo, José (Revista Historia de la Educación Latinoamericana, 2014)
The paper proposes topics of an analysis and interpretation of student mobilizations carried out in Chile during 2011, which replaced in the center of the national political debate, the value and the need to strengthen public education, challenging policies and neoliberal reforms developed since 1981 and deepened during the democratic governments of the period 1990-2010. It analyzes from the perspective of the history of education, the main role of the university in both the organizational and political capacity, as in the claims proposed by the university social movement.